BIOLOGICAL AND CHEMICAL MANAGEMENT OF PHYTOPHTHORA ROOT ROT /COLLAR ROT IN CITRUS NURSERY - R. M. GADE, (The Bioscan, 2012)
Citrus jambhiri Lush is the most widely used root stock for most of citrus scion in India. Soil samples were collected from nurseries of Vidarbha region in India. Almost all samples were found associated with P. parasitica (28-46 cfu/g soil) when tested on PARPH medium. Rangpur lime was found tolerant root stock whereas, Citrus jambhiri was found susceptible to the disease. In vitro antagonism showed that P. parasitica significantly inhib- ited by T. harzianum and T. virens (84.96%). However, intensity of antagonism was different as per medium. There was a continuous reduction in pathogen population from 41 to 8 propagules/g soil with reduction in root rot /collar rot in Citurs jambhiri. All Thirty seven native isolates of Pseudomonas spp. were found positive for production of IAA, HCN and Siderophore. Pf XXVI (16.80%) and Pf IV (24.10%) were found effective to manage the disease in addition to increased growth response under glass house condition. Among chemicals, seed treatment with Metalaxyl @2.5 g/ Kg seed f.b. spraying of metalaxyl at 45 and 90 days after emergence was effective to manage the disease (8.56%).